Investigation of optimized network splitting of large-scale urban centralized heating system operation - Wei Zhong; Jiaying Chen; Yi Zhou; Zhongbo Li; Zitao Yu; Xiaojie Lin (Energy Reports, 2020)
Operation optimization is a critical issue in the management of the multi-source large-scale urban centralized heating system (UCHS). A major challenge is to deal with the complex topological structure of its heating network. We investigate the operation enhancement of UCHS from the view of network splitting. We carry out the network splitting analysis of UCHS by establishing its heating network model and corresponding simulation platform based on graph theory. We validate the model against experimental data in a city located in northern China, and further use the model to show the effectiveness of network splitting by calculating its energy consumption indices under different splitting schemes. Simulation results show that the optimal network splitting scheme could improve the load distribution among the heating sources and reduce the operation cost. We apply the scheme during the 2018-2019 heating season and compare the results with the previous season operated by its existing scheme. The optimized scheme reduces heat supply requirements for heating sources and improves the load distribution among heating sources. With the weather condition change considered, seasonal accumulated area specific daily heat supply is reduced by 3.9%. Overall, seasonal natural gas consumption is reduced by 16.8%.
Keywords: 330; Operation scheme; Splitting optimization; Urban centralized heating system